The effect of weight training on the physical performance of Boxers at junior level of Kaithal District (Haryana, India) - Solanki, Ajay (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The main purpose of the study is to know the effects of weight training programme on the physical performance of boxers at junior level of Kaithal district. For the purpose of the study 10 selected exercises of weight training along with warming up and cooling down exercises schedule of one hour’s and one and half an hour in both morning and evening session were used. The investigator himself with the help of his colleagues implemented training schedule for 10 weeks to experiment group consisting of 20 boxers. The training designed in such a way that physical fitness required for the boxing situations, ranging from technical and tactical requirement for the boxers. To develop physical fitness, the training of physical parameters like strength, power and endurance spread over a number of years. But due to various constraints and restrain on the investigator, the training of weight was confined to 10 weeks only. The data was collected of we and post test of the boxers appeared in the physical fitness components test given in the preceding paras. Boxer whatever their weight categories are, they need physical efficiency and fitness elements as they have to fight against the odds in the boxing ring. They are to contribute physically for complete coordination among themselves. The boxers get no respite in the course of bout when fighting or daging boxing in the ring. Boxers requires great stamina, speed, endurance, flexibility and agility with greater amount of strength and power and to meet the demand, it has to be cultivated through proper exercises not only during preparatory phases or stages but one’s long boxing career. In addition with relaxation and optimum workload through weight during competition period, one has to maintain vigor and stamina and speed. Which is a matter of training while strength can be earned through light weight exercises and squats with weight and with carrying of dumbbells etc.